LIFE WITH COVID-19: SWOT ANALYSES FOR TRANSFORMATIVE DIGITAL LEARNING IN EDUCATORS’ PERSPECTIVE - Vindača, Olga; Ļubkina, Velta; Abuže, Anda; Ušča, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Covid-19 pandemic has influenced all fields of life, including education, teaching and learning procedure. Initially the situation seemed vague and uncertain, but still challengeable, by moving almost all processes online and offering the digital or distance learning. The aim of the article to identify key aspects of distance learning from educator’s perspective following Covid-19 and basing on the research results to offer transformative digital learning strategy for educational institution. The authors draw attention to the procedure how to re-direct weakness and threats into strengths and opportunities, by implementing necessary changes at four indicated levels: individual, institutional, local government and state one. An important part for any strategy creation, including transformative digital learning (TDL) strategy for educational institution, is the detailed situation analyses. SWOT analysis structure has been offered by analyzing respondents’ views for the conducted online questionnaire for educators and experts’ interviews Additionally literature review has been made to create the list of key elements necessary for the TDL strategy development, including global networking providers and nowadays paradigm shift –the transformative one